Status social subjetivo, consumo de alimentos e obesidade: estudo longitudinal de saúde do adulto (ELSA-BRASIL) - Josi Fernandes de Castro Rodrigues (2013)
INTRODUCTION: Subjective social status (SSS) reflects the perception that the individual has its location in the social hierarchy and has been used to better understand the socioeconomic gradient in health. OBJECTIVE: The aim of this study was to investigate whether low SSS is associated with low consumption of fruits and vegetables, the habitual consumption of meat with excess fat and obesity, after adjustment for demographic and socioeconomic variables. METHODS: This was a cross sectional study conducted with adults aged 35 to 64 years of age (n = 13,514), participants from baseline (2008-2010) of the Longitudinal Study of Adult Health (ELSA-Brasil). The dependent variables were: low consumption of fruits and vegetables, habitual consumption of meat with excess fat, overall obesity (BMI 30 kg/m2) and abdominal obesity (waist to height ratio 0.5). The main explanatory variable was measured by the SSS of three "ladders" with 10 steps according to the contexts of the society, community and work. The variables were adjusted for age, self-reported skin color, educational level and net family income. Odds ratios (OR) and the 95% confidence intervals were obtained by multiple logistic regression for gender specific. RESULTS: In men, the SSS in the three ladders was associated low consumption of fruits and vegetables, the habitual consumption of meat with excess fat, after adjustment, the SSS in the three ladders associated the low consumption of fruits and vegetables and SSS on the ladder of society remained associated the habitual consumption of meat with excess fat. In women, the SSS in the three ladders was associated low consumption of fruits and vegetables, the habitual consumption of meat with excess fat and waist to height ratio 0.5, the SSS on the ladders society and the community was associated for general obesity, after adjustment, the SSS on the ladders society and work remained associated the habitual consumption of meat with excess fat. The perceived availability of fruits and vegetables in the neighborhood did not attenuate the magnitude of the association between SSS and consumption of fruits and vegetables. CONCLUSIONS: Our results extend the knowledge about the use of subjective social status as an indicator of socioeconomic condition, showing its importance to represent different aspects of social inequities in men and women.